FINANCIAL LITERACY AND FINANCIAL TECHNOLOGY ON INDIVIDUAL FINANCIAL BEHAVIOR THROUGH FINANCIAL INCLUSION AMONG LECTURERS AND EMPLOYEES OF A PRIVATE UNIVERSITY IN BANDUNG CITY - Windi Novianti; M. Yani Syafei; Umi Narimawati (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2025)
This study examines the effect of Financial Literacy and Financial Technology on Individual Financial Behavior through Financial Inclusion. Today, individuals have the right to determine the steps they will take in financial decision-making. Various new and diverse financial products are emerging, requiring individuals to have a deeper understanding if they wish to utilize them. This is necessary to avoid financial decisions that may be detrimental. Individual finances can be well-managed if financial behavior is accountable. Strategic efforts are needed to enhance individuals' financial knowledge. The use of technology facilitates financial transactions. Through financial literacy and financial technology, individuals can improve their financial behavior. Moreover, financial inclusion plays a crucial role in promoting positive financial behavior. Access to financial services enables middle and lower-income individuals to save and invest. This study is a quantitative research employing observation and questionnaire methods. The questionnaire serves as a data collection technique in which respondents are given written questions or statements to answer. The respondents in this study are lecturers and employees working at a private university in Bandung City. The sampling method used is purposive sampling. To obtain an accurate and direct representation of the lecturers and employees, this study utilizes a survey system. The total population of lecturers and employees at the university is 325 individuals. Using Slovin’s formula, a sample of 77 respondents, consisting of lecturers and employees, was determined. After conducting analysis and discussion on the data processing results, it can be concluded that Financial Literacy and Financial Technology have a significant positive effect on Financial Inclusion. However, Financial Technology does not have a significant impact on Individual Financial Behavior. The effect of financial technology on individual financial behavior is not always positive and depends on how the technology is utilized. Therefore, individuals must understand the risks and benefits of financial technology and use it wisely to improve their financial behavior.